The Effect of Dettol Soap Television Advertisment to Gender Myth Through Semiotics - Tiarma Ika Yuliana; Astri Indriana Octavita Haryanto; Rima Novia Ulfa (Pusat Penerjemah dan Penyunting Universitas Indraprasta PGRI, 2023)
Advertisement is a form of mass communication. Advertisements contain about language, whether verbal and non-verbal. For that reason, advertisements can also analyze by language theories, like semiotic. Most television commercials portray the patriarchy of common perceptions where men make decisions for women and there is no place for gender equality. This work illustrates the analysis of the bold